2004
DOI: 10.2355/isijinternational.44.1669
|View full text |Cite
|
Sign up to set email alerts
|

Reoxidation of Al-Ti Containing Steels by CaO-Al2O3-MgO-SiO2 Slag

Abstract: Reoxidation of liquid steel containing Al and Ti by 14%CaO-35%Al 2 O 3 -10%MgO-41%SiO 2 (in mass%) slag was investigated at 1 823 K with initial Al content of 820 mass ppm and Ti content varied from 100 to 500 mass ppm. It was observed that Al and Ti in the steel were simultaneously oxidized by SiO 2 in the slag, and the soluble oxygen was supersaturated during the course, particularly with respect to Al. Based on the experimental results, a new mechanism of the reoxidation reaction was proposed, which involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 12 publications
4
57
1
Order By: Relevance
“…The Ti-rich and Al-rich phases are encapsulated in a thin but continuous shell of pure Al2O3. Similar complex inclusions were also reported by Park et al 4) and Doo et al 5) from a sample taken at the RH-OB degasser after Ti addition, where they were believed to be in liquid state (at least inner side). The overall chemical composition (Ti#) of the inner side of the inclusion is about 0.66-0.76 as defined above, Ti/(Ti+Al/2), which is in good agreement with the present results.…”
Section: Existence Of Liquid Ti-al-o Oxide Inclusionssupporting
confidence: 85%
See 1 more Smart Citation
“…The Ti-rich and Al-rich phases are encapsulated in a thin but continuous shell of pure Al2O3. Similar complex inclusions were also reported by Park et al 4) and Doo et al 5) from a sample taken at the RH-OB degasser after Ti addition, where they were believed to be in liquid state (at least inner side). The overall chemical composition (Ti#) of the inner side of the inclusion is about 0.66-0.76 as defined above, Ti/(Ti+Al/2), which is in good agreement with the present results.…”
Section: Existence Of Liquid Ti-al-o Oxide Inclusionssupporting
confidence: 85%
“…For this reason, the interaction between existing NMI in liquid steel and the various installations is in the center of attention for secondary refining process. Recently, details of the inclusion formation of Ti-alloyed Al-killed steel grades [1][2][3][4][5] and its physical and chemical development during reoxidation are receiving considerable attention. From these studies, it is being recognized that inclusions in the Al-Ti-Fe-O system may react sensitively on the details of the secondary steelmaking treatment, such as the oxygen balance achieved.…”
Section: Introductionmentioning
confidence: 99%
“…(Thermodynamic calculations using FactSage 6) show that neither Mn nor Si form oxide inclusions under their experimental conditions). Park et al 34) also observed Al-Ti-O inclusions during reoxidation experiments on Alkilled and Ti-bearing steel at 1 600°C. In their study, twolayered inclusions of an unknown Al-Ti-O phase covering a core Al 2 O 3 solid were frequently observed.…”
Section: Al 2 O 3 -Ti 2 O 3 Binary Systemmentioning
confidence: 90%
“…This evolution is believed to be due to the selective oxidation sequence of element during the experiments. [20][21][22] Since the original steel contains around 400 ppm [Al] and 700 ppm [Ti], oxygen supplied from the gunning material preferably reacts with [Al] to form Al 2 O 3 (as shown in Fig. 6).…”
Section: Qualitative Assessment Of Inclusion Evolutionmentioning
confidence: 99%